White matter hyperintensities predict response to language treatment in post-stroke aphasia - Varkanitsa, Maria (Neurorehabil Neural Repair, 2020)
BACKGROUND. White matter hyperintensities (WMH) are a radiological marker of brain health that has been associated with language status in post-stroke aphasia; however, its association with language treatment outcomes remains unknown. OBJECTIVE. To determine whether WMH in the right hemisphere (RH) predict response to language therapy independently from demographics and stroke lesion-related factors in post-stroke aphasia. METHODS. We used the Fazekas scale to rate WMH in the RH in 30 patients with post-stroke aphasia who received language treatment. We developed ordinal regression models to examine language treatment effects as a function of WMH severity after controlling for aphasia severity, stroke lesion volume, time post onset, age and education level. We also evaluated associations between WMH severity and both pre-treatment naming ability and executive function. RESULTS. The severity of WMH in the RH predicted treatment response independently from demographic and stroke-related factors such that patients with less severe WMH exhibited better treatment outcome. WMH scores were not significantly correlated with pre-treatment language scores, but they were significantly correlated with pre-treatment scores of executive function. CONCLUSION. We suggest that the severity of WMH in the RH is a clinically relevant predictor of treatment response in this population.